Style: notes on the transformation of a concept - Hvattum, Mari 1966- (2019)
Style has been a key concept in architectural discourse since the 18th century, yet its meaning is far from unequivocal. This essay traces the shifting meanings attributed to style in German architectural thinking from the mid-18th to the early 19th century. Reading and discussing texts by J.J. Winckelmann, J.W. Goethe, C.C. Hirschfeld, A.W. Schlegel, H. Hübsch, and F. Eisenlohr, I study the multifarious uses to which style was put in this period and look at the effects these uses had on architecture.